SISTEM INFORMASI E-LEARNING KURSUS KOMPUTER PADA LKP OBY KOMPUTER TEMBILAHAN - Edward; Samsudin (Indragiri Islamic University, 2021)
In carrying out teaching and learning activities at course institutions, an instructor must have been faced with various problems both from internal and external factors. One real example of problems from external factors that are happening at this time is the Corona Virus (COVID-19) pandemic. A dangerous disease whose transmission is very fast has made almost all countries impose lockdowns to deal with the transmission of the virus. With the enactment of the Lockdown status, it has an impact on education, especially teaching and learning activities. In response to this, the government urges the teaching and learning process to be carried out at home using internet media. In order to keep learning in the midst of the current pandemic, the researcher who is also a computer course instructor at the Oby Computer Course and Training Institute (LKP) has designed a website. E-learning. Through the information system Website E-Learning computer course at LKP OBY Computer aims to analyze, design and implement a distance computer course learning system. The use of the Waterfall method as a system development method functions as a mechanism to identify software, as well as UML (Unified Modeling Language) as modeling, and uses the PIECES method to facilitate researchers in building systems. Information Systems Website E-Learning computer courses at LKP OBY Computer Tembilahan can make it easier for students to carry out the learning process using online methods.